KEPEMIMPINAN LURAH DALAM MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DAERAH DI KELURAHAN LABUH BARU BARAT KECAMATAN PAYUNG SEKAKI KOTA PEKANBARU TAHUN 2015-2016 - ", Hambali; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted on July 20, 2016 at the launching of Community Gotong Royong Bulan Bakong Masyarakat (BBGRM) XIII and PKK 44th Day of PKK held at Taman Kota Bungin Koto Village, Kuantan Singingi. West Labuh Baru Subdistrict, Payung Sekaki District, Pekanbaru City get the highest award at Riau Province level. The community in West Labuh Baru village has implemented the spirit of Mutual Cooperation to build the region. This is one form of leadership success in managing the leadership of community leaders based on the spirit of mutual help in building the region.The purpose of this research is to know the leadership of Lurah in increasing the community participation in regional development and to know the leadership of Lurah in policy or development initiative in Sub-district of Labuh Baru Barat Kecamatan Payung Sekaki Pekanbaru City. The location of this research was conducted in West Labuh Baru Subdistrict, Payung Sekaki Sub District, Pekanbaru City. The method used in this research is descriptive method with qualitative approach. Data collection techniques in this study are interviews and documentation. Data analysis technique used is descriptive qualitative data analysis.The results of this research Leadership Lurah in improving community participation in regional development in West Labuh New Village to approach the community using persuasive techniques in government leadership and communicative techniques in government leadership. Lurah leadership style run by H. Lukman Hakim, SP also shows the power style. In terms of using his power as Lurah, his leadership style implies a participatory or democratic style. The Leadership Initiative of the New West Labuh Village in Development, namely: Creating Community Activities, Physical Development Initiatives through Cooperation with Local Community Organizations (CSOs).Keywords: Leadership Village, Community Participation, Development.